Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan (Studi Kasus Divisi Pemasaran dan SDM di PDAM Surya Sembada Kota Surabaya) - Haris Hermawan Pradana (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
An employee commitment depends on the work environment's concern and work motivation that has a close relationship with satisfaction to achieve these goals. Thus, the physical and mental aspects involved in every human being's work. This study aimed to determine how much influence the work environment and motivation on employee job satisfaction. This study takes in PDAM Surya Sembada City of Surabaya - a regional drinking water company located in Mayjend Prof. Dr Moestopo No 2. It is a company known as a provider of clean water services in Surabaya, which formed in 1976. The data collected by interviews, questionnaire, observation, and documentation. The sampling technique is non-probability. The statistical analysis is a multiple regression using SPSS. Based on the descriptive analysis test results with the three-box method category, the employee work environment variables and work motivation of employees in PDAM Surya Sembada Kota Surabaya included in the medium category.